Membrane dissolution and division in P - Damien Woods; Niall Murphy; Mario J. Pérez-Jiménez; Agustín Riscos-Núñez (Springer Berlin / Heidelberg, 2009)
Membrane systems with dividing and dissolving membranes are known to solve PSPACE problems in polynomial time. However, we give a P upperbound on an important restriction of such systems. In particular we examine systems with dissolution, elementary division and where each membrane initially has at most one child membrane. Even though such systems may create exponentially many membranes, each with different contents, we show that their power is upperbounded by P. This work is supported by a Project of Excellence TIC-581 from the Junta de Andalucía, project TIN 2006 13425 of Ministerio de Educación y Ciencia of Spain, and the Irish Research Council for Science, Engineering and Technology.